2019
DOI: 10.1021/acssuschemeng.8b06544
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interfacial Charge Transfer Dynamics and Onset Shift in Nanostructured Hematite Photoanodes via Efficient Ti4+/Sn4+ Heterogeneous Self-Doping Through Controlled TiO2 Underlayers

Abstract: We introduce a simple strategy to unintentional heterogeneous Ti4+/Sn4+ doping and surface passivation of hematite via TiO2 underlayers at high temperature quenching. The effects of the controlled TiO2 underlayer thickness and high temperature quenching process on the interfacial diffusion of Ti4+/Sn4+ and TiO2 passivation of hematite nanorod arrays have been carefully studied. The improved photoelectrochemical water oxidation performance of the TiO2 underlayered hematite nanorod photoanodes after high-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…[106][107][108][109][110][111][112][113][114][115][116] Meanwhile, other researchers spared no effort in correlating PEC performance improvement with the surface states evolution upon doping or coating of a secondary semiconductor onto hematite photoanodes. [117][118][119][120][121][122][123][124][125][126][127][128] For instance, D. Monllor-Satoca et al prepared mesoporous hematite-titania composite films by mixing the respective preformed nanoparticles obtained by a non-aqueous solgel route in a wide range of loading levels (0-20 mol %). Voltammetric and EIS were performed observing an optimum 10% doping, with a 15-fold photocurrent increase (up to 1.3 mA cm -2 at 1.23 V vs RHE) and a 100-fold decrease of the charge transfer resistance.…”
Section: Kinetic Isotope Effect (Kie)mentioning
confidence: 99%
“…[106][107][108][109][110][111][112][113][114][115][116] Meanwhile, other researchers spared no effort in correlating PEC performance improvement with the surface states evolution upon doping or coating of a secondary semiconductor onto hematite photoanodes. [117][118][119][120][121][122][123][124][125][126][127][128] For instance, D. Monllor-Satoca et al prepared mesoporous hematite-titania composite films by mixing the respective preformed nanoparticles obtained by a non-aqueous solgel route in a wide range of loading levels (0-20 mol %). Voltammetric and EIS were performed observing an optimum 10% doping, with a 15-fold photocurrent increase (up to 1.3 mA cm -2 at 1.23 V vs RHE) and a 100-fold decrease of the charge transfer resistance.…”
Section: Kinetic Isotope Effect (Kie)mentioning
confidence: 99%
“…Therein, the decreased photocurrent density is probably because that the thicker Ti 3 C 2 MXene underlayer will hinder the diffusion of Sn 4 + from FTO substrate and electron forward transfer [24 , 39] . As reported in previous study, Park et al found that the thick TiO 2 underlayer could greatly hinder the diffusion of Sn 4 + , consequently acting as a dominant factor in reducing the photocurrent density of hematite [39] . While, for the anodic shift in onset potential, it is possibly due to the surface effects of Ti species via the diffusion through bulk hematite to surface, which will increase the surface trapping states of hematite photoanode [39 , 40] .…”
Section: Resultsmentioning
confidence: 51%
“…While, for the anodic shift in onset potential, it is possibly due to the surface effects of Ti species via the diffusion through bulk hematite to surface, which will increase the surface trapping states of hematite photoanode [39 , 40] . This conclusion strongly indicates that the optimum thickness of Ti 3 C 2 MXene underlayer should balance the suppression of interfacial charge recombination and electron transfer from hematite to FTO substrate [39] . Meanwhile, the thickness of hematite nanostructure may affect the PEC performance of Ti-Fe 2 O 3 photoanode, and consequently which has also been optimized by controlling the concentration of FeCl 3 •6H 2 O in the precursor solution for the hydrothermal growth of FeOOH film.…”
Section: Resultsmentioning
confidence: 88%
“…In this vein, the tin diffusion length limit has been studied by different research groups 35,62,69–71 . For instance, ionic exchanges can be observed in Figure 4A, where the behavior of Sn diffusion in the semiconductor matrix was detailed by the line profile obtained from cross‐section TEM‐EDS analysis (Figure 4B) of hematite nanoceramics.…”
Section: Sn‐modified Hematite Photoanodesmentioning
confidence: 99%